Increased Risk for Respiratory Complications in Male Extremely Preterm Infants: A Propensity Score Matching Study - Su, Zhiwen; Lin, Lili; Fan, Xi; Jia, Chunhong; Shi, Bijun; Huang, Xiaoxia; Wei, Jianwei; Cui, Qiliang; Wu, Fan (Frontiers in Endocrinology, 2022)
Background: Currently, conclusions about the effect of sex on the clinical outcome of extremely premature infants (EPI) are inconsistent. This study used propensity score matching to evaluate the effect of sex on the clinical outcome of EPI. Methods: A retrospective analysis was performed on EPI treated in the Department of Neonatology of The Third Affiliated Hospital of Guangzhou Medical University from 2011 to 2020. The patients were divided into male and female groups and then divided into subgroups based on gestational age (GA) and birth weight (BW). Nine confounding factors, including GA, BW, 1-minute Apgar score≤3, withdrawal treatment, mechanical ventilation, duration of mechanical ventilation, mother with advanced age (age≥35 years), complete-course antenatal steroid therapy and hypertensive disorders of pregnancy, were matched at a ratio of 1:1 by using the propensity score matching method. The survival rate at discharge and the incidence of major hospitalization complications were compared between the two groups. Results: After matching the confounding factors, compared with the female group, there was no significant difference in the survival rate at discharge, the mortality of activating treatment and withdrawing treatment in the male group (all P＞0.05). Additionally, the incidence of RDS, BPD and moderate to severe BPD in the male group were significantly increased (all p＜0.01), especially among male infants with birth weight of 750 to 999 g. Conclusions: Compared with females, male EPI have a higher risk of respiratory complications, particularly at 750-999 g of birth weight